HUBUNGAN INTERAKSI SOSIAL MAHASISWA PGSD TERHADAP MOTIVASI BELAJAR PADA MASA PANDEMI DI UNIVERSITAS - Putri Julia; Anwar, Faisal; Herni Yuanda (Jurnal Sociohumaniora Kodepena (JSK), 2022)
Social interaction of students at higher education can affect the activities of students both in academic activities or in the learning process which in every learning process there needs to be good social interaction between students and other students this can affect the process of student learning activities and their learning motivation . A person's motivation to learn can arise with encouragement both from within the individual and outside the individual. The purpose of this study is to find out whether there is a relationship between social interaction of PGSD students batch 2020 with learning motivation during the pandemic at the Serambi Mekkah University. Quantitative research approach and types of correlation research. The population in this study were all PGSD students of the 2017-2021 class and the sample in this study was from the population, namely the 2020 students of the Serambi Mekkah University, totaling 48 students. The data collection technique is a questionnaire. Based on the results of the research, the correlation value obtained is 0.48, which means that the social interaction relationship between PGSD students batch 2020 and learning motivation during the pandemic is sufficient or moderate. The results of the analysis of the t-test value = 3.7099 and t-table = 1.6786 so that it can be concluded that there is a relationship between the social interaction of PGSD students batch 2020 with motivation to learn during the pandemic at the University of Serambi Mekkah